Dinamika Permasalahan Skizofrenia Paranoid Melalui Paradigma Humanistik: Studi Kasus - Nerissa Arviana (LPPM Universitas Proklamasi 45, 2023)
ABSTRACT Schizophrenia is a persistent psychotic disorder that includes disorders of behavior, thoughts, emotions, and perceptions. Paranoid schizophrenic is usually characterized by delusions of persecution. There are various background that support paranoid schizophrenic. One of the back ground could be explained through humanistic paradigm based on the theory of Carl Roger. Carl Rogers explained that every human being needs to be loved and accepted or called get a positive regard. Positive regards from parents would determine the personality of the children whether conditional or unconditional positive regards. The aim of this research is to determine the dynamics of the problems people with paranoid schizophrenia through humanistic paradigm approach. This is a single case qualitative research with case study as its method. Datas of research are retrieved integration techniques, which is combined observation, interview, and psychological tests. This study shows that paranoid schizophrenia is caused by the lost of dependency object who usually protect schizophrenic’s self-esteem. Conditional positive regards are the former caused of paranoid schizophrenia. As the absence of emotion focused coping and withdrawal tendency caused by conditional positive regards from parents, schizophrenic would form a delusion of persecution to maintain their self-esteem when the depencency object is gone. Delusions of persecution is used to decrease the incongruency between actual self and ideal self.